β-sitosterol ameliorates myocardial infarction injury via modulating the NF-κB and necroptosis signaling pathways - Xu, Jia-jia; Chen, Min-wei; Lai, Long-zhen; Xiao, Di; Jiang, Shu-yan; Lin, Jun-xin; Zhang, Zheng-hao; Shan, Zhong-gui (Frontiers in Pharmacology, 2026)
IntroductionAcute myocardial infarction (MI) is a leading global cause of morbidity and mortality, where inflammatory response and programmed cell death (PCD) are critical in disease progression. β-sitosterol (β-SITO), a phytosterol with known cardioprotective effects, has been implicated in cardiovascular diseases, but its specific role and mechanisms in MI remain underexplored.MethodsThis study employed both in vivo and in vitro models. Male C57BL/6J mice with MI were used to evaluate the effects of β-SITO treatment. Cardiac function was assessed via echocardiography, infarct size and fibrosis were analyzed histologically. In vitro, cardiomyocyte viability under hypoxia and TGF-β-induced cardiac fibroblast activation were examined. Mechanistic insights were gained through transcriptomic profiling, molecular docking studies, and validation by Western blotting.Resultsβ-SITO treatment significantly reduced myocardial infarct size, alleviated cardiac fibrosis, and improved cardiac function in MI mice. In vitro, it enhanced cardiomyocyte viability under hypoxia and inhibited TGF-β-induced fibroblast activation. Transcriptomic analysis revealed that β-SITO modulated pathways related to immune-inflammatory responses, NF-κB, and necroptosis signaling. Molecular docking confirmed its strong binding affinity to key components of these pathways. Western blotting validated the inhibition of NF-κB activation and necroptosis in both hypoxic cardiomyocytes and MI mouse heart tissue.Conclusionβ-SITO demonstrates significant therapeutic potential for improving post-MI recovery. Its cardioprotective effects are likely mediated through the modulation of NF-κB and necroptosis signaling pathways, highlighting it as a promising candidate for MI treatment.